"I want to become part of the Australian community": Challenging the marginalisation of women resettled as refugees in Australia – Findings from a photovoice project. Issue 3 (7th October 2021) - Lumbus, Anita; Fleay, Caroline; Hartley, Lisa K.; Gower, Shelley; Creado, Andrea; Dantas, Jaya A. R.
Abstract: This article discusses a community‐based participatory research (CPBR) project, which used photovoice to explore 43 refugee women's perspectives of settlement in Perth, Western Australia. The research was conducted between a university and a multicultural women's health service from 2016 to 17. The women were given cameras and chose topics to photograph, which represented their settlement experiences and, using reflective group dialogue, reflected on their settlement successes and challenges and provided policy recommendations for improving the settlement process. Eleven women were interviewed for further in‐depth reflections, and 22 women selected photographs and wrote accompanying narratives for a travelling photography exhibition. Key themes of the importance of English language learning and family support during the settlement process are explored. Drawing on intersectionality and postcolonial feminist theories, this article discusses how government provisions for English education are incongruent with the settlement needs of women and access to family reunion is largely unattainable, which has negative implications for women's health and well‐being. This article demonstrates how government policy marginalises women and reinforces an existing gendered, racial hierarchy. An intersectional approach to settlement policymaking and programmes is recommended for women's successful settlement.